ANALISIS PEMUTUSAN HUBUNGAN KERJA SEPIHAK ATAS DASAR PELARANGAN HAK PEKERJA DALAM BERSERIKAT (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NO.815K/PDT.SUS-PHI/2016) - Jerisca Shandy Nicolas; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2020)
Layoff is a scary thing for workers. Many companies terminate their employment unilaterally, which is not in accordance with Law No. 13 of 2003 concerning Manpower. The problem faced is how the reasons for layoffs against workers are based on PHI Invitation Law Number 13 of 2003 and Supreme Court Decree No. 815 K / Pdt.Sus-PHI / 2016. The research method used in this study is the normative legal research method. The results showed that the reasons for layoffs of workers based on Law Number 13 of 2003 concerning Labor are quite a lot of them, referring to Article 162-172 of Law Number 13 of 2003 concerning Employment: resignation properly on their own volition, resignation in writing of their own volition due to layoff, resignation due to reaching retirement age, workers make serious mistakes, workers are held by the authorities, the company / company suffers losses, workers are lost to follow-up, workers die, workers commit violations, there are changes in status , merger, softening or changing ownership and layoffs due to efficiency reasons and the Supreme Court Decree No. 815 K / Pdt.Sus-PHI / 2016, where PT Wira Wisata Indah - Royal Regal Hotel did layoffs due to efficiency reasons. PT Wira Wisata Indah - Hotel Royal Regal Jakarta has carried out unilateral layoffs without a clear legal basis, and the layoffs conducted by the Defendant also contravened Law Number 21 of 2000 concerning Trade Unions / Trade Unions Article 28 point (a).